Evaluation of the Prescription Pattern of Antimicrobial Agents in Hospitalised Paediatric Patients in a Tertiary Care Hospital of Kathmandu, Nepal - Khadka, Anjan; Rayamajhi, Heleena; Shrestha, Shova (Journal of Nepal Paediatric Society, 2018)
Introduction: Infectious diseases are one of the most frequent reasons for hospital admission for children and antimicrobials are commonly used to treat them. There is higher prevalence of irrational prescriptions of antimicrobials in such population. This study was conducted to survey the pattern of antimicrobial prescription in Paediatric inpatient. Material and Methods: This was retrospective, descriptive, observational study. The data was collected from prescription records. The paediatric population included in the study was categorised into three age groups. A total of 87 prescriptions were studied and the information was recorded in performa. Data were recorded in MS Excel and Graph Pad Prism version 6 was used for analysis. Results: The number of male child was outnumbered by female child. The average age of the patient on antimicrobial prescription was 5.34 ± 2.18 years. The mean duration of hospital stay was 6.17 ± 2.01 days. The common indications for antimicrobial prescriptions were upper respiratory tract infections, diarrhoeal illness, urinary tract infections, enteric fever, etc. The antimicrobials prescription rate was 1.33. Oral route was found to be commonly used than parenteral route. The generic prescription rate was 33.6%. The most common drug prescribed was ceftriaxone followed by amoxicillin + clavulanic acid, ciprofloxacin, metronidazole and amikacin. The 62.5% of antimicrobials were prescribed from National Essential List of Medicines. Conclusion: This study highlights the prescription pattern of antimicrobial agents in hospitalised Paediatric population in a tertiary care hospital.